Enhancing the stability of peat soil through treatment with pond ash-hydrated lime under varying soaking durations - Zeety Md Yusof; Mohamad Afiq Let; Muhammad Ikmal Mohd Noh; Nur Shafiqah Abdullah; Nazaruddin Abdul Taha (Semarak Ilmu Publishing, 2025)
Peat soil poses significant challenges for civil engineering construction due to its unfavorable characteristics, including high compressibility, high water content, low shear strength, and settlement issues. Consequently, it is often considered unsuitable for infrastructure projects such as roads and foundations. However, there is a need to improve peat soil to make it viable for supporting foundations. Hydrated lime (HL) is a commonly used material for chemical stabilization in soil engineering due to its abundance worldwide. Additionally, pond ash (PA), an eco-friendly by-product, is used in the construction industry. Combining HL and PA offers a promising solution to address ground settlement issues related to soft soil like peat. This study’s objective was to modify peat soil by binding PA and HL together and to investigate the effect of this admixture on the strength of the modified peat soil. The index property tests such as moisture content, organic content, fiber content, specific gravity, and pH test were conducted to understand the initial characteristics of the peat soil. The unconfined compressive strength (UCS) test samples were prepared using steel split molds and subjected to the UCS test to analyses their strength. Sample could soak for different durations (0, 7, 14, 28, and 60 days) before testing. The variation in PA and HL content, the PA content was kept constant at 5%, 10%, 15%, and 20%. The HL content varied in four different compositions 3%, 6%, 9%, and 12%. The laboratory work findings show that the compressive strength of the treated peat soil increases with increasing PA-HL content and soak time. The sample mixed with 15% and 20% PA, combined with various compositions of HL and soaking times exceeding about 2 months, exhibited awe-inspiring strength. This study examined the challenges associated with peat soil and presented an environmentally friendly approach by utilizing by-products like PA. Continuously improving the engineering properties of peat soil can significantly reduce the environmental impact of construction activities while ensuring the stability and longevity of infrastructure projects.